Pulmonary support strategies and options for improving lung function in term neonates: warning signs of damage. Issue 3 (June 2010) - Attar, Mohammad; Donn, Steven M
Term newborn infants with lung injury have varying degrees of pulmonary edema, increased airway resistance and uneven distribution of atelectasis contributing to decreased pulmonary compliance and functional residual capacity. Lung injury is often initiated by the inflammatory process associated with the primary etiology of respiratory failure and is further exacerbated by ventilator-induced lung injury. Volutrauma, atelectotrauma and, to a lesser extent, barotrauma and rheotrauma contribute to inducing biotrauma, which is lung injury that results from uncontrolled inflammation. Recognizing the mechanisms of lung injury and the pattern and limitations of measured changes in lung function and mechanics might also serve as indicators of lung injury and are important in the formulation of lung protective strategies. Maintaining adequate functional residual capacity (open lung strategy), assuring appropriate tidal volumes to avoid both atelectotrauma and volutrauma and avoiding excessive exposure to oxygen should help achieve this goal.